2014
DOI: 10.3945/jn.113.186676
|View full text |Cite|
|
Sign up to set email alerts
|

β-Carotene-9′,10′-Oxygenase Status Modulates the Impact of Dietary Tomato and Lycopene on Hepatic Nuclear Receptor–, Stress-, and Metabolism-Related Gene Expression in Mice

Abstract: Tomato and lycopene (ψ,ψ-carotene) consumption is hypothesized to protect against nonalcoholic steatohepatitis and hepatocarcinogenesis, processes that may depend upon diet and gene interactions. To investigate the interaction of tomato or lycopene feeding with β-carotene-9',10'-monooxygenase (Bco2) on hepatic metabolic and signaling pathways, male wild-type (WT) and Bco2(-/-) mice (3-wk-old; n = 36) were fed semi-purified control, 10% tomato powder-containing, or 0.25% lycopene beadlet-containing diets for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 45 publications
4
29
1
1
Order By: Relevance
“…Nevertheless, it should be noted that lycopene effects on PPARa-and PPARg-mediated signaling were relatively modest; thus, this might explain why lycopene did not reduce final BW. Lycopene modulations in PPAR-associated signaling were observed in the adrenal glands, liver, and kidney of rodents in previous studies (16,50,51). During the preparation of this manuscript, a recent publication by Tan et al (50) showed that 3wk-old BCO2-KO male mice on a lycopene-supplemented (250 mg/ kg diet) AIN-93G semipurified diet for 3 wk modulated hepatic PPAR-associated signaling that could potentially affect hepatic responses to metabolic, infectious, or chemical stress.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, it should be noted that lycopene effects on PPARa-and PPARg-mediated signaling were relatively modest; thus, this might explain why lycopene did not reduce final BW. Lycopene modulations in PPAR-associated signaling were observed in the adrenal glands, liver, and kidney of rodents in previous studies (16,50,51). During the preparation of this manuscript, a recent publication by Tan et al (50) showed that 3wk-old BCO2-KO male mice on a lycopene-supplemented (250 mg/ kg diet) AIN-93G semipurified diet for 3 wk modulated hepatic PPAR-associated signaling that could potentially affect hepatic responses to metabolic, infectious, or chemical stress.…”
Section: Discussionmentioning
confidence: 90%
“…Male TRAMP (+/-) C57BL/6×FVB/N hybrid and male C57BL/6 controls (Jackson Laboratory, Bar Harbor, ME) were used. Tomato and lycopene diets were formulated to provide blood and tissue concentrations of lycopene similar to humans (19). TRAMP mice weaned at 4 wk-of-age were randomized to one of three semi-purified AIN-93G-based diets (ResearchDiets, New Brunswick, NJ) with either 0.25% ( w/w ) placebo beadlets (DSM, Basel, Switzerland), 10% ( w/w ) tomato powder providing 384 mg lycopene/kg diet (FutureCeuticals, Momence, IL ) [with 0.25% ( w/w ) placebo beadlets], or 0.25% ( w/w ) lycopene beadlets (RediVivo 10% lycopene, DSM) providing 462 mg lycopene/kg diet, as previously described (19).…”
Section: Methodsmentioning
confidence: 99%
“…The induction of cell differentiation (52) via the restoration of gap junctions (57) has also been suggested. Other mechanisms include prevention of oxidative damage (58,59) , inhibition of angiogenesis (59,60) , induction of phase II enzymes (61)(62)(63) , interaction with growth factors and sex hormones (64) and the induction of nuclear receptors activation (65)(66)(67) . Lycopene has also been found to confer photoprotection (68) .…”
Section: Mechanistic Studiesmentioning
confidence: 99%